2009
DOI: 10.1289/ehp.11342
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Bisphenol A Alters Early Adipogenesis in the Rat

Abstract: BackgroundThe causes of the current obesity pandemic have not been fully elucidated. Implication of environmental endocrine disruptors such as bisphenol A (BPA) on adipose tissue development has been poorly investigated.ObjectivesThe aim of the present study was to evaluate the effects of perinatal exposure to BPA on early adipose storage at weaning.MethodsPregnant Sprague-Dawley rats had access to drinking water containing 1 mg/L BPA from day 6 of gestation through the end of lactation. Pups were weaned on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
293
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(322 citation statements)
references
References 53 publications
24
293
0
5
Order By: Relevance
“…The adolescent rats exposed to DEHP resulted higher body weight is identical to others results of study. The available data verified that treated with a low dose of endocrine disruptors during adolescent development can interfere with the normal homeostasis of the endocrine system, and may lead to the occurrence of overweight and obesity [27][28][29]. The function of THs is energy metabolism regulation and the levels of those were decreased with DEHP exposure, this is possible to be a cause for fat accumulation.…”
Section: Discussionmentioning
confidence: 55%
“…The adolescent rats exposed to DEHP resulted higher body weight is identical to others results of study. The available data verified that treated with a low dose of endocrine disruptors during adolescent development can interfere with the normal homeostasis of the endocrine system, and may lead to the occurrence of overweight and obesity [27][28][29]. The function of THs is energy metabolism regulation and the levels of those were decreased with DEHP exposure, this is possible to be a cause for fat accumulation.…”
Section: Discussionmentioning
confidence: 55%
“…Body weight increased in all experimental groups, however at the end of the procedure, the treated ones with BPA and exendin-4 had lower weight compared with the control. Some writers revealed a correlation between BPA exposure and body weight elevation (19,20). This result may be explained by the fact that several important mechanisms may affect body weight including, glucose uptakes and homeostasis, adipocyte deposition, dose and duration of treatment, gender and species (21).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Sakurai et al [71], a high dose of BPA has been revealed to stimulate an increase in the glucose transporter and glucose uptake into adipocytes in cell culture. Study showed that perinatal exposure to a low dose of BPA increased adipogenesis in female rats at weaning [72].…”
Section: Other Miscellaneous Efectsmentioning
confidence: 99%